2021
DOI: 10.1155/2021/8894222
|View full text |Cite
|
Sign up to set email alerts
|

Multiview Self-Supervised Segmentation for OARs Delineation in Radiotherapy

Abstract: Radiotherapy has become a common treatment option for head and neck (H&N) cancer, and organs at risk (OARs) need to be delineated to implement a high conformal dose distribution. Manual drawing of OARs is time consuming and inaccurate, so automatic drawing based on deep learning models has been proposed to accurately delineate the OARs. However, state-of-the-art performance usually requires a decent amount of delineation, but collecting pixel-level manual delineations is labor intensive and may not be nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…These results showed that our model was comparable to previously published studies for HN OAR segmentation regarding the DSC [ 19 ] ( Table 4 ), and also to other studies using partially labeled or unlabeled datasets and following similar approaches to ours [ 7 , 11 , 25 ]. Almost all OARs reached a performance close to the maximum DSC reported in the literature, outstanding in some cases such as the temporomandibular joints and inner ears.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results showed that our model was comparable to previously published studies for HN OAR segmentation regarding the DSC [ 19 ] ( Table 4 ), and also to other studies using partially labeled or unlabeled datasets and following similar approaches to ours [ 7 , 11 , 25 ]. Almost all OARs reached a performance close to the maximum DSC reported in the literature, outstanding in some cases such as the temporomandibular joints and inner ears.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, this process is thoroughly subjected to inter- and intra-practitioner variabilities [ 6 , 9 , 10 ] driven by diverse factors such as experience, availability, quality, and interpretation of diagnostic imaging [ 4 ]. The limited soft tissue contrast of computed tomography (CT) images is also a substantial problem in HN delineation [ 10 , 11 ], as many OARs have similar densities to fat, muscle, or other surrounding tissues. Segmenting these OARs, such as the parotid or submandibular glands, is particularly challenging [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of self-supervised networks mitigates the effect of this issue. 30,31 A fascinating development in machine learning is the invention of a technique called GANs, 10 in which two models compete with each other to make their predictions more accurate. Since their debut in 2014, GANs have excelled in generative image modeling and demonstrated exceptional performance across various medical imaging applications, including classification 32,33 and segmentation.…”
Section: Related Workmentioning
confidence: 99%
“…The scarcity of labeled data in medical imaging is really affecting the performance of deep learning models. The introduction of self‐supervised networks mitigates the effect of this issue 30,31 …”
Section: Related Workmentioning
confidence: 99%